Molecular Detection of High Risk Human Papilloma Virus Subtypes in Neoplastic Cervical Tissues - Kamaluddin, Nor Rizan (2007)
Human papillomavirus (HPV) plays an important role in the pathogenesis of cervical cancer. HPV has been found in 99.7% of cervical cancers worldwide. This common virus is easily transmitted by genital skin-to skin and sexual contact. The HPVs that infect the genital mucosa are classified according to their oncogenic potential and are described as either high or low-risk. The detection of E7 oncogene transcripts of high-risk human papillomavirus type 16, 18, 31, 33, 35, 39, 45, 51, 52 and 56 may be a sensitive indicator of the direct involvement of viral oncogenes in the development of cervical intraepithelial neoplasia and carcinoma. Three methods were used in this study; Type Specific PCR, Dot-blot hybridization to prove no false positive of the TS-PCR products and SyBr Green Real Time PCR to detect and identify the multiple infection of the HPV subtypes. The objectives of this study are i) to determine the prevalence and the types of human papillomavirus in the neoplastic cervical tissues patients, ii) to detect and identify the multiple infections of HPV subtypes. Paraffin embedded tissues was collected from Hospital Universiti Kebangsaan Malaysia. All 67 specimens from several stages; Cervical intraepithelial neoplasia CIN I, CIN II, CIN III and carcinoma were screened for the presence of high risk HPV types. To determine the presence of HPV in the samples, Type Specific PCR (TS-PCR) and dot blot hybridization were performed. Positive samples from the TS-PCR and dot blot hybridization were analyzed and identified for the presence of the two prevalent HPV genotypes such as HPV 16 and HPV 18 using the SyBr Green Real-Time PCR. The results showed, in 67 samples, CIN I was detected in 37/67 (55%), CIN II was detected in 12/67 (18%), CIN III was detected in 15/67 (22%) and in 3/67 (5%) patients, invasive carcinoma was found. Because of the multiple infections, 67 HPV genomes were found in the 57 positive samples using TS-PCR. HPV 16 genome was detected in 55/67 (82%) cases, HPV 18 in 8/67 (12%) cases, HPV 33 was detected in 1/67 (1.5%), HPV 51 was detected in 1/67 (1.5%) and HPV 56 in 2/67 (3%) and 8 cases had multiple infections. The results showed DNA melting curve for HPV 16 was having a peak around 80.2º ± 0.2C and threshold Ct value for specific product of HPV-16 was 20 ± 1 cycles whereas DNA melting curve for HPV 18 was having a peak around 79.2 ± 0.2ºC and threshold cycle Ct value for specific product of HPV 18 was 22 ± 1 cycles. In conclusion, HPV- 16 was the most prevalent followed by HPV-18. This study detected five subtypes of high risk HPV; HPV 16, 18, 33, 51 and 56. HPV types 31, 35, 39, 45 and 52 were not detected. A SyBr Green Real-Time PCR method has the potential for clinical usage in prescreening, detection and identification of HPV infection in the cervical neoplasia at different stages of the disease.